No job for a lady: women directors in Hollywood - Williams, Rachel L. (2001)
This thesis explores the position of female film directors working in Hollywood. It is intended to address an area in feminist film theory which has often been overlooked. Although it is incorrect to say there has been no feminist analysis of the "mainstream" woman director, most of the work which has been done concentrates either on finding the feminism or femininity of her films, or studies only a select few directors. This research widens the debate by validating the study of all women directors, and moves away from the search for definitive feminist meaning in the cinematic text. It employs a contextual and multi-theoretical approach to interrogate the multiplicity of meanings embodied by the phrase "woman director".